Consider electromagnetic waves polarized in the direction propagating in one dimension in an active laser medium with current density J ( x ) . Maxwell's equation for the z -component of the electric field of these waves then reads
( d x 2 d 2 − κ 2 ) E z ( x ) = J ( x )
for κ some constant. Suppose there is a source at x = 0 and that there is a conducting mirror far away so that effectively E z ( 0 ) = 1 and E z ( ∞ ) = 0 are the boundary conditions. Find the Green's function G ( x , y ) for x < y that will allow for determination of the electric field anywhere in space.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This is wrong. The green function G(0,y)=0 is the correct selection.
Log in to reply
No, I believe the original solution is correct. We do not have Dirichlet boundary conditions in this problem, unlike the example in the wiki this problem is used in. The boundary condition G(0,y) = 0 is not the correct boundary condition to use. In this problem we have added a source at x=0 instead of a conducting mirror, which changes the boundary conditions as given in the problem statement.
Problem Loading...
Note Loading...
Set Loading...
The homogeneous equation is solved by the general expression:
G ( x , y ) = { c 1 e κ x + c 2 e − κ x , d 1 e κ x + d 2 e − κ x , x < y x > y .
The boundary conditions G ( 0 , y ) = 1 , G ( ∞ , y ) = 0 impose the constraints on the coefficients:
c 1 + c 2 d 1 = 0 = 1
Solving for c 2 and d 2 and plugging into the expression for G ( x , y ) yields:
G ( x , y ) = { 2 c 1 sinh ( κ x ) + e − κ x , d 2 e − κ x , x < y x > y .
Enforcing continuity at x = y gives:
2 c 1 sinh ( κ y ) + e − κ y = d 2 e − κ y ,
and requiring the derivative to jump by unity yields:
− κ d 2 e − κ y − 2 c 1 κ cosh ( κ y ) + κ e − κ y = 1 .
Solving the two conditions for c 1 , d 1 yields:
c 1 d 2 = − 2 κ e − κ y = 1 − κ sinh ( κ y )
Plugging c 1 into G ( x , y ) for x < y , find the result:
G ( x , y ) = e − κ x − κ e − κ y sinh ( κ x ) , x < y ,
as claimed.